Single-cell transcriptomics analysis reveals a disrupted NK-T cell interaction network in liver metastatic cancer - Xiaoshuang Wang; Zhongen Wu; Yan Zhou; Dehua Yang; Qingtong Zhou; Di Zhu; Ming-Wei Wang; Lu Wang (Scientific Reports)
Abstract Natural killer (NK) cells and T cells play crucial roles in liver metastatic cancer, particularly through their cytotoxic effects on tumor cells. Although existing evidence suggests a functional network of mutual regulation between NK and T cells, the nature of their interaction and its role in liver metastasis remain elusive. In this study, we analyzed single-cell transcriptomics of liver metastases and adjacent tissues from nasopharyngeal carcinoma (NPC), thyroid carcinoma (THCA), breast cancer (BC), colorectal cancer (CRC) and cervical cancer (CESC) to uncover the NK-T cell interaction network and its functional implications. In adjacent tissues, we observed increased infiltration of CD8+ NKT-like cells, γδT cells, and NK cells. The interaction between CD8+ NKT-like cells, CD8+ T cells, γδT cells, and NK cells were enhanced, with stronger signals associated with T and NK cell functions. Notably, CD8+ NKT-like cells, CD8+ T cells, and γδT cells exhibited an increased capacity to activate NK cells. These T cell subsets promoted NK cell anti-tumor activity via CD48-CD244 and TNF-TNFR signaling pathways, which in turn activated the ERK, JNK, and MAPK cascades. Our findings provide valuable insights into the NK-T cell interaction network in liver metastatic cancer, highlighting its potential as a therapeutic target.